2018
DOI: 10.1177/0363546518759052
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Jump Training Augmented With Body Weight Support After ACL Reconstruction: A Randomized Controlled Trial

Abstract: Jump training is an efficacious intervention for athletes with poor outcomes after ACL reconstruction, and training with body weight support lessens the risk for excessive joint stress during practice. Registration: NCT02148172 ( ClinicalTrials.gov identifier).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…Isometric maximal voluntary muscle contraction balance control and muscle strength of hamstring and quadriceps were also highly significant. The present study showed significant effectiveness in quantitative parameters like kinematic gait parameters and maximum activation of quadriceps and hamstring by Zult et al 9 and Elias et al 17 and with p value 0.015 and 0.001 respectively.…”
Section: Effectiveness Of Various Active Physical Therapy On Qualitative Measuresupporting
confidence: 49%
See 4 more Smart Citations
“…Isometric maximal voluntary muscle contraction balance control and muscle strength of hamstring and quadriceps were also highly significant. The present study showed significant effectiveness in quantitative parameters like kinematic gait parameters and maximum activation of quadriceps and hamstring by Zult et al 9 and Elias et al 17 and with p value 0.015 and 0.001 respectively.…”
Section: Effectiveness Of Various Active Physical Therapy On Qualitative Measuresupporting
confidence: 49%
“…Most significant effect was seen in study by Capin et al 12 and Hallworth et al 16 who used therapies like ACL SPORT-Protocol and A standardized protocol with DVD given to subjects respectively. Kinetic gait parameter was significant in the study by Elias et al including vertical ground reaction force as well by Moran U et al Present showed significant effectiveness in quantitative parameters like kinetic gait parameters, any one disability scale, by Elias et al 17 and Capin et al 12 with p value 0.05 and 0.002 respectively.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations